2013
DOI: 10.1177/1046496413489735
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Faultlines in Geographically Dispersed Teams

Abstract: Faultlines have the potential to significantly disrupt team performance due to the creation of intergroup bias. In geographically dispersed teams, given the combination of dispersed locations and other diversity characteristics, faultlines are potentially a major issue that needs to be more fully understood. This study examines the impact of faultlines on geographically dispersed teams and how problems caused by faultlines can be resolved. An experimental study of 40, four-person student teams finds that perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 64 publications
1
54
0
1
Order By: Relevance
“…Generally, scholars have found that strong faultlines negatively influence group processes and outcomes (e.g., cohesion, performance; Jehn & Bezrukova, 2010; Molleman, 2005). Since Thatcher and Patel’s (2012) review, scholars have continued to explore the impact of faultlines on group outcomes (e.g., performance, decision-making; Bezrukova, Spell, Caldwell, & Burger, 2016; Spoelma & Ellis, 2017), group processes (e.g., cohesion, conflict; Chiu & Staples, 2013; Schölmerich, Schermuly, & Deller, 2016), perceptions (e.g., climate perception; Beus, Jarrett, Bergman, & Payne, 2012), and behaviors (e.g., knowledge exchange; Lim, Busenitz, & Chidambaram, 2013). Although most faultlines research focuses on the effects of faultlines on groups, some recent studies have investigated how faultlines affect individuals and organizations (e.g., employees’ loyal behavior, organizational performance; Bezrukova et al, 2016; Chung, Liao, Jackson, Subramony, Colakoglu, & Jiang, 2015).…”
Section: An Overview Of Multidimensionalitymentioning
confidence: 99%
“…Generally, scholars have found that strong faultlines negatively influence group processes and outcomes (e.g., cohesion, performance; Jehn & Bezrukova, 2010; Molleman, 2005). Since Thatcher and Patel’s (2012) review, scholars have continued to explore the impact of faultlines on group outcomes (e.g., performance, decision-making; Bezrukova, Spell, Caldwell, & Burger, 2016; Spoelma & Ellis, 2017), group processes (e.g., cohesion, conflict; Chiu & Staples, 2013; Schölmerich, Schermuly, & Deller, 2016), perceptions (e.g., climate perception; Beus, Jarrett, Bergman, & Payne, 2012), and behaviors (e.g., knowledge exchange; Lim, Busenitz, & Chidambaram, 2013). Although most faultlines research focuses on the effects of faultlines on groups, some recent studies have investigated how faultlines affect individuals and organizations (e.g., employees’ loyal behavior, organizational performance; Bezrukova et al, 2016; Chung, Liao, Jackson, Subramony, Colakoglu, & Jiang, 2015).…”
Section: An Overview Of Multidimensionalitymentioning
confidence: 99%
“…Examining both the perception of subgroups and processes alleviating the effects of faultlines is necessary for understanding the mechanisms and consequences of subgroups in global teams. Research on faultlines and subgroups is frequently conducted in the lab (e.g., Chiu & Staples, 2013; Yilmaz & Peña, 2014) and although this contribution is very important, subgroups should also be examined in field studies.…”
mentioning
confidence: 99%
“…To this point, the first takeaway from this period is that focus on the Virtual Teams cluster (Cluster 2) intensified in line with the increased use of CMC and virtual teams throughout organizations and broader society (Tannenbaum et al, 2012). For example, in line with the broad applicability of the phenomenon, work on virtual teams further expanded into that on decision-making (McLeod, 2013), group diversity (Martins & Shalley, 2011), cultural diversity (Han & Beyerlein, 2016), training (Gilson et al, 2013), faultlines (Chiu & Staples, 2013), and group dynamics (Handke et al, 2019). This integration signals the promise and peril of virtual teams.…”
Section: Resultsmentioning
confidence: 99%